Advances in 3D Thin‐Film Li‐Ion Batteries. Issue 15 (16th July 2019) - Moitzheim, Sébastien; Put, Brecht; Vereecken, Philippe M.
Abstract: The status and progress toward solid‐state 3D thin‐film Li‐ion microbatteries is reviewed. Planar thin‐film batteries (TFBs) are commercially available. A major issue with planar TFBs, however, is that the total footprint capacity is limited, as only a relatively small electrode volume is available for energy storage. Coating of the complete battery thin‐film stack, i.e., cathode/solid electrolyte/anode, over a 3D microstructured current collector substrate can provide higher footprint capacity as a result of the surface area enhancement. However, thus far, no 3D TFB with footprint capacity exceeding the limit of ≈250 µAh cm −2 are achieved. The authors provide a status of the individual components: thin‐film cathodes, anodes, and thin‐film solid electrolyte conformally coated over 3D substrates with periodic microstructures. Guidance for designing a 3D TFB with optimum capacity is also provided. Abstract : 3D thin‐film batteries are solid‐state microbatteries where a thin‐film stack of cathode/solid‐electrolyte/anode is conformally coated over a 3D substrate and bottom current collector for increased footprint capacity while maintaining the high speed charging properties of thin‐film electrodes.